Pengembangan Multimedia Interaktif pada Pembelajaran Menulis Cerita Rakyat Berbasis Literasi Siswa Kelas X SMA Swasta Al-Hidayah Medan - Ayuwaningsih, Windy; Rita, Rita; Safina, Nila (Medan Resource Center, 2024)
This study aims to: (1) Describe the development of interactive multimedia for teaching folklore (saga) writing based on literacy for Class X students at SMA Al-Hidayah Medan. (2) Assess the feasibility of the developed interactive multimedia for teaching folklore (saga) writing based on literacy for Class X students at SMA Al-Hidayah Medan. (3) Evaluate the effectiveness of the interactive multimedia product for teaching folklore (saga) writing based on literacy for Class X students at SMA Al-Hidayah Medan. The research follows the DDD-E model (Decide, Design, Develop, and Evaluate). The participants include content experts, media design experts, graphic design experts, Indonesian language teachers, and Class X students at SMA Al-Hidayah Medan. Validation results from content experts indicate very good criteria for content feasibility (81.2%), presentation feasibility (90%), language usage (83.3%), and graphic design (87.5%). The overall assessment places the interactive multimedia for teaching folklore (saga) writing based on literacy in the